Prevalence of diabetic peripheral neuropathy among type 2 diabetes mellitus and its associated factors in a primary care clinic in Malacca: a cross-sectional study - Ali, Hanifatiyah; May, Janarisa Mustar; Yein, Lee Ping; Abdul Rashid, Aneesa (Universiti Putra Malaysia Press, 2024)
Introduction: Diabetes peripheral neuropathy (DPN) is the commonest diabetic complication. This study aimed to determine the prevalence of diabetic peripheral neuropathy among type 2 diabetes mellitus patients and its associated factors in a primary care clinic. Materials and methods: A cross sectional study was done in a government funded primary care clinic in Melaka involving type 2 diabetes mellitus patients aged 18 years and above using a systematic random sampling. Multiple logistic regression analysis was performed to identify its associated factors. Results: 493 respondents were involved in the study with a median age of 62 (IQR 14) and 43.4% per cent (n=214) male. The prevalence of DPN in this study was 58.4% per cent (n=288). Age (OR:1.05; 95% per cent CI: 1.04 – 1.07), insulin treatment (OR: 3.28; 95% per cent CI: 1.99 – 5.40), and presence of albuminuria (OR:1.74; 95% per cent CI: 1.17 – 2.60) were found to be significantly associated with DPN. Conclusion: The prevalence of DPN is high in primary care setting in Malaysia. To enhance detection of DPN, multimodal foot examination should be performed especially among patients aged >60 years old, those on insulin treatment and those with presence of albuminuria